A prospective international cooperative information technology platform built using open-source tools for improving the access to and safety of bone marrow transplantation in low- and middle-income countries. (8th April 2014) - Agarwal, Rajat Kumar; Sedai, Amit; Dhimal, Sunil; Ankita, Kumari; Clemente, Luigi; Siddique, Sulman; Yaqub, Naila; Khalid, Sadaf; Itrat, Fatima; Khan, Anwar; Gilani, Sarah Khan; Marwah, Priya; et al.
Abstract: Jagriti Innovations developed a collaboration tool in partnership with the Cure2Children Foundation that has been used by health professionals in Italy, Pakistan, and India for the collaborative management of patients undergoing bone marrow transplantation (BMT) for thalassemia major since August 2008. This online open-access database covers data recording, analyzing, and reporting besides enabling knowledge exchange, telemedicine, capacity building, and quality assurance. As of February 2014, over 2400 patients have been registered and 112 BMTs have been performed with outcomes comparable to international standards, but at a fraction of the cost. This approach avoids medical emigration and contributes to local healthcare strengthening and competitiveness. This paper presents the experience and clinical outcomes associated with the use of this platform built using open-source tools and focusing on a locally pertinent tertiary care procedure—BMT.